Islam and customs in Minangkabau: Analysis of the Indigenous Concept of Basandi Syarak, Syarak Basandi Kitabullah (in the Perspective of Buya Hamka and A.A. Navis) - Abdul Aziz Romdhoni (Penerbit Hellow Pustaka, 2026)
This research discusses the concept of Adat Basandi Syarak, Syarak Basandi Kitabullah (ABS–SBK) from the perspective of Buya Hamka and criticism by A.A. Navis towards its application in Minangkabau society. Buya Hamka views ABS-SBK as an ideal foundation that emphasizes harmonious integration between customs and Islamic law. According to him, customs function as social tools that gain legitimacy as long as they are based on the values of the Koran and Sunnah, as emphasized in the QS. An-Nisa' verse 59. In this view, Islam is the main source of values, while custom is a means of implementing moral values and justice in social life. In contrast, A.A. Navis expressed criticism of the ABS-SBK practice, which was considered to often stop at a symbolic level and had not been fully realized consistently in social reality. He highlighted the deviations that occur when customs and religion are exploited for the sake of power or social status, thus deviating from the moral substance of Islam as emphasized in the Prophet's hadith regarding adhering to the Qur'an and Sunnah. A comparison of the two figures shows that their differences are complementary: Hamka emphasizes the normative and philosophical dimensions, while Navis emphasizes the empirical and evaluative dimensions. Thus, the ABS-SBK concept remains relevant as an integrative framework between customs and religion, as long as it is accompanied by moral commitment and real implementation in facing the social dynamics of contemporary Minangkabau society.